PENILAIAN KINERJA TROTOAR BERDASARKAN LEVEL OF SERVICE (LOS) (STUDI KASUS: JALAN PERMINDO, KOTA PADANG) - Fithriyah Patriotika; Miftahul Aulia (Jurnal Applied Science in Civil Engineering, 2025)
This study aims to evaluate the performance of sidewalks on Permindo Street, Padang City, using the Level of Service (LoS) approach. Data were collected through field surveys conducted over three days, from 17 to 19 October 2025, during three different time periods representing morning, midday, and evening peak hours. The data collected included pedestrian flow and the availability of pedestrian space in each observation segment. The analysis results show that on Friday, 17 October 2025, in segment 1, the available pedestrian space reached 14.2 m²/ped with a maximum pedestrian flow of 1.3 ped/min/m. Referring to the Regulation of the Ministry of Public Works (Permen PUPR) 2014, this condition corresponds to a Level of Service category A. On other days, the measured pedestrian space availability was 8.3, 10, and 11.1 m²/ped, which were classified as Level of Service B because they met the minimum space standard of ? 3.6 m²/ped. Overall, the sidewalk performance on Permindo Street is categorized as good, although variations in service levels occur at certain times and conditions.